Performing the digital : performance studies and performances in digital cultures - Beyes, Timon; Leeker, Martina; Schipper, Imanuel (Transcript-Verlag, 2017)
How is performativity shaped by digital media - and how do performance practices themselves reflect and alter techno-social configurations? "Performing the Digital" inquires into the technological terms and conditions of performance and performance studies and maps and theorizes the registers of performance at work in digital cultures. The contributions range from the performativity of algorithms and digital devices to the modulation of affect, atmospheres and the body; from performing cities, protest, organization and the economy to the scholarly performances of research.